Cyber Crime dan Tingkat Kepercayaan Terhadap Penggunaan Produk E-Banking - Pakpahan, Roganda Andreas; Fauzi, Achmad; Nursal, Fadhli; Prasetyo, Ade Ilham; Mayki, Crist Doohan Ananda; Marwan, Benaya Aushaf Razan Putra; Sihombing, Immanuel Pharosandika; Laurence, Michael (Prisani Cendekia, 2024)
In an increasingly digital era, e-banking has become an integral part of financial life, but concerns regarding information security and online fraud are increasing. This research aims to understand how cyber crime attacks, such as phishing and identity theft, influence users' perceptions and trust in the security of e-banking products. Through data analysis and interviews, this research tries to identify factors that influence users' level of trust and offers useful insights for financial service providers in increasing user security and trust in e-banking